1980
DOI: 10.2135/cropsci1980.0011183x002000050030x
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic Effects of Sodium Azide in Rice1

Abstract: Seeds of rice (Oryza sativa L. spp. japonica) cultivar ‘M5’ were presoaked in distilled water and treated for 2 or 3 hours with 0, 0.12, 0.50, 0.75, 1.0, 1.25, 1.50, and 1.75 mM sodium azide solutions prepared in 0.1 M phosphate buffer (pH 3). After treatment the seeds were rinsed for 1 hour in 15 C tap water. Seeds receiving a 2‐hour azide treatment were redried in a fume hood at room temperature for 24, 48, 72, and 96 hours prior to planting to develop treatment procedures suitable for transporting dry, trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 0 publications
1
30
0
1
Order By: Relevance
“…Earlier workers reported a higher frequency of albina mutants in rice (Swaminathan et al 1970, Nanda and Misra 1975, Madhu sudhana Rao and Manmada Rao 1983. However, a higher frequency of viridis than albina was reported by Afsar Awan et al (1980) in azide treated japonica cultivar M5 and Seetharami Reddi and Reddi (1984) in MMS, dMS, dEMS and dES treated indica cultivars, T(N) 1, IR 8 and Sona.…”
Section: Mutagenic Efficiency and Effectivenessmentioning
confidence: 83%
See 1 more Smart Citation
“…Earlier workers reported a higher frequency of albina mutants in rice (Swaminathan et al 1970, Nanda and Misra 1975, Madhu sudhana Rao and Manmada Rao 1983. However, a higher frequency of viridis than albina was reported by Afsar Awan et al (1980) in azide treated japonica cultivar M5 and Seetharami Reddi and Reddi (1984) in MMS, dMS, dEMS and dES treated indica cultivars, T(N) 1, IR 8 and Sona.…”
Section: Mutagenic Efficiency and Effectivenessmentioning
confidence: 83%
“…The corresponding values were 52.1 and 18.6 percent in IET 5656 and 23.5 and 6.6 percent in Fujiminori. Sarma et al (1979) and Afsar Awan et al (1980) reported that in sodium azide treated rice, the maximum frequency of chlorophyll mutation was 42.0 (per M1 panicles) and 7.8 (per M2 seedlings), respectively. The high frequency of mut tants observed in the present study with 24 hours presoaking suggests that mutation frequencies in rice are also enhanced by treatments of pregerminated seeds.…”
Section: Mutagenic Efficiency and Effectivenessmentioning
confidence: 99%
“…In general, mutagenic treatments had resulted in decreased mean coupled with enhanced variability in both genotypes and generations as compared to their respective control, though the magnitude of shift in mean varied with the treatment, genotype and trait. The decline in means of treated population was demonstrated in rice (Jana and Roy, 1973;Awan et al, 1980;Siddiqui and Singh, 2010).…”
Section: Grain Yield Per Plantmentioning
confidence: 99%
“…There are several reports on the effect of physical and chemical mutagens on the size, shape, and color of the seeds (Mohanasundaram et al 2001 ;Joshi and Verma 2004 ). Dwarf, short culm, and early fl owering mutants were induced in rice by azide treatment (Awan et al 1980 ).…”
Section: Morphological Mutationsmentioning
confidence: 99%